Carbon Capture and Storage associated with Enhanced Oil Recovery: A review - Barbosa Coelho, Nathalia; Meneguelo, Ana Paula; de Lorena Diniz Chaves, Gisele (Latin American Journal of Energy Research, 2022)
The mitigation of climate change is a trend topic studied and discussed around the world. However, the sustainable supply of energy and materials is not a reality, given the accelerated growth of energy demand, which considerably intensifies the emission of Greenhouse Gases (GHG). In this sense, among the technologies that can be allied to reduce GHG emissions is the capture and geological storage of carbon dioxide - CCS (Carbon Capture and Storage). In addition to reducing GHG emissions, a CCS project can be applied in oil production to improve well performance in the Enhanced Oil Recovery (EOR) process. The objective of this paper is to review the concepts and technologies related to Carbon Capture and Storage and Enhanced Oil Recovery, from a systematic literature review, structuring and classifying the selected papers. To this end, the SYSMAP (Scientometric and Systematic Yielding Mapping Process) technique was applied to structure the main stages of the review. In addition, the Science Mapping method was used to identify the works with the greatest impact in the area of interest, through the R Studio software, Bibliometrix and International Indicators proposed by Capes. It was evident that the technical approach was the most employed, followed by the economic approach, and finally the environmental approach. Some limitations and proposals for future studies were identified. Thus, the contribution of this paper involves identifying the most relevant studies in the area and, through structured analysis, presenting the state of the art guiding future research.